Customer engagement: Developing an innovative research that has scholarly impact. Issue 3 (3rd July 2018) - Brodie, Roderick J.; Juric, Biljana
Abstract: This essay outlines the development of a stream of research about customer engagement that is having a substantial scholarly impact. We explore the conditions to achieve this success which includes the critical role of the theorizing process. The theorizing process is the core to crafting two seminal contributions. Implications for achieving innovative research that has a scholarly impact concludes the essay.